Why Michel Foucault in Norwegian Special-Education Research? - Hege Knudsmoen; Eva Simonsen (Nordic Journal of Social Research)
This article seeks to identify what impact the works of Michel Foucault have had on special-education research in Norway. We also discuss what his writings may contribute to future research.  Foucault’s perspectives are far from dominant in special-education research today. We present research within the relevant social sciences which has been influenced by Foucault and which has had impact on special-education research. We aim to demonstrate that Foucault’s genealogy of ethics may bring new insights and a new critical approach to special-education research. The ethics of inclusion are particularly constructive and productive in both pedagogy and special-education research. In the discussion of Foucault’s relevance in special-education research, we focus on his texts on governmentality to conduct and govern a learner and the ethics of inclusion. The mode of subjectivity highlights the productive nature of disciplinary power – how it names and categorizes learners, the conduct of conduct or how learners govern themselves under education.